Halfway home: race, punishment, and the afterlife of mass incarceration - Miller, Reuben Jonathan (Little, Brown and Company)
Something like an introduction -- I: Debt. Confessions ; Guilt ; Sinnerman -- II: Wage. Millions of details ; In victory and spectacular defeat ; Chains and corpses -- III: Salvation. Treatment ; Power ; America, goddamn!